The Lancashire cotton industry and its rivals : international competition in cotton goods in the late nineteenth century : Britain versus India, China, and Japan - Kawakatsu, Heita, 1948-; LTCB International Library Trust; Kokusai Bunka Kaikan (Tokyo, Japan) (Tokyo : International House of Japan, 2018)
Includes bibliographical references (pages 305-319) and index